The role of project manager in smes for developing new product by e-collaboration - Mohammadjafari, M.; Ahmed, Shamsuddin; Md Dawal, Siti Zawiah; Zayandehroodi, H. (2012)
The research in this paper is based seeks to understand how manufacturing companies can accomplish of their projects in the real time with less cost. This paper describes a new model using critical success factors of implementing projects in the small and medium size enterprises (SMEs). The factors in conceptual model were identified in past studies and validate from the survey by interview with 20 project management in electronic industries in Iran. Several prior researches have suggested some critical success factors for reducing time and cost in new product. These factors are departments of product, planning, procurement and design. However, none of these studies has proposed a model that specifies practices that should be undertaken to facilitate the progression to reduce time and cost in new product in SMEs. Following this, a development of a new model is supposed important to help SMEs understand what is required in order to be an effective global organization in terms of reduce time and cost by electronic collaboration (E-collaboration) through project management.